Spectrophotometric evaluation of hemolysis in plasma by quantification of free oxyhemoglobin, methemoglobin, and methemalbumin in presence of bilirubin. Issue 5 (13th February 2021) - Heckl, Christian; Lang, Alexander; Rühm, Adrian; Sroka, Ronald; Duffield, Thomas; Vogeser, Michael; Paal, Michael
Abstract: Severe intravascular hemolysis leads to the simultaneous presence of free heme pigments (oxyhemoglobin, methemoglobin, and methemalbumin) and bilirubin in human plasma. Standard spectrophotometric methods used to assess in vivo hemolysis inadequately address this complex analytical situation. Thus, we propose a novel quantification algorithm to ensure the highest analytical specificity. A corresponding second‐derivative fitting algorithm was validated according to the guideline of bioanalytical method validation from the European Medicines Agency using plasma specimens (n = 1759) spiked with different concentrations of oxyhemoglobin and methemoglobin. The results were compared to standard spectrophotometric quantification methods described by Harboe, Noe, and Fairbanks. Based on the second‐derivative method, simultaneous quantification of oxyhemoglobin and methemoglobin/methemalbumin in samples with total bilirubin concentrations ≤4.9 mg/dL (83.8 μmol/L) provided robust results (inaccuracy ≤20%, imprecision ≤16%). Analyzing UV/VIS spectra of plasma from patients with confirmed severe intravascular hemolysis evidenced an underestimation of up to 33% for the combined free heme pigment content. The employed second‐derivative algorithm allows for automated and highly specific quantification of the free heme pigment content in diluted human plasma, which cannot be realized with standard spectrophotometric evaluation methods. An Excel‐based tool readily applicable to clinical datasets accompanies this manuscript. Abstract : Cell‐free oxyhemoglobin is a very specific marker for intravascular hemolysis. However, standard spectrophotometric methods inadequately address the presence of methemoglobin and methemalbumin that are indicative of severe intravascular hemolysis with rapid hemoglobin breakdown. We hereby present a second‐derivative spectrophotometric method for the simultaneous quantification of oxyhemoglobin, methemoglobin, and methemalbumin using UV/VIS spectra recorded from diluted plasma specimens.